Healing of saccular aneurysms following platinum coil embolization: lack of improved efficacy with vitamin C supplementation. (22nd August 2012) - Dai, Daying; Yong-Hong, Ding; Rezek, Issa; Lewis, Debra A; Kallmes, David F; Kadirvel, Ramanathan
Abstract : Background and purpose: To test the hypothesis that systemic administration of vitamin C, through its action of stimulating collagen synthesis and crosslinking, would decrease the recurrence and improve the occlusion of experimental aneurysms treated with platinum coils. Methods: Experimental aneurysms were created in female rabbits and were embolized with platinum coils (>30% packing density). The animals were divided into three groups: group 1 (n=6) rabbits served as controls, group 2 (n=5) rabbits were fed with a vitamin C supplemented feed and group 3 (n=8) rabbits were medicated with vitamin C pills. Digital subtraction angiography was used to evaluate stability after embolization. Subjects were euthanized at 12 weeks after coil implantation, and serum vitamin C levels were then measured. Histological samples were examined with a grading system (range 0–12) based on the neck and dome features. Masson Trichrome staining was used to evaluate collagen deposition. Parametric data were analyzed with one way analysis of variance and non-parametric data were examined using a Kruskal–Wallis test. Results: There were no significant differences between groups in mean aneurysm size. Mean serum vitamin C concentration was significantly higher in group 3 and group 2 compared with group 1, while vitamin C levels between group 2 and group 3 were statistically comparable. Coil compaction was noted in one of six subjects in group 1 and in three of eight subjects in group 3. All of the remaining aneurysms in the test and control groups showed stable occlusion. There were no significant differences in histological scores or collagen deposition among groups. Conclusions: Vitamin C supplementation following platinum coil embolization does not demonstrate improvement of long term occlusion rates of aneurysms.